2018
DOI: 10.1093/cercor/bhy315
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Onset Age of Visual Deprivation on Visual Cortex Surface Area Across-Species

Abstract: Blindness early in life induces permanent alterations in brain anatomy, including reduced surface area of primary visual cortex (V1). Bilateral enucleation early in development causes greater reductions in primary visual cortex surface area than at later times. However, the time at which cortical surface area expansion is no longer sensitive to enucleation is not clearly established, despite being an important milestone for cortical development. Using histological and MRI techniques, we investigated how reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 63 publications
2
11
1
1
Order By: Relevance
“…Similar findings were observed using histological analyses for V1, V2M and sc. These results are consistent with previous histological studies in anophthalmic and enucleated mice (Masse et al., 2014), anophthalmic rats (Bravo & Inzunza, 1994), enucleated rats (Andelin et al., 2018; Laing et al., 2012) as well as histological (Bock et al., 2012) and MRI (Andelin et al., 2018) studies in enucleated ferrets showing a smaller V1 (volume or area) in blind compared with sighted animals. Studies in early blind humans have also shown smaller visual structures.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar findings were observed using histological analyses for V1, V2M and sc. These results are consistent with previous histological studies in anophthalmic and enucleated mice (Masse et al., 2014), anophthalmic rats (Bravo & Inzunza, 1994), enucleated rats (Andelin et al., 2018; Laing et al., 2012) as well as histological (Bock et al., 2012) and MRI (Andelin et al., 2018) studies in enucleated ferrets showing a smaller V1 (volume or area) in blind compared with sighted animals. Studies in early blind humans have also shown smaller visual structures.…”
Section: Discussionsupporting
confidence: 91%
“…Studies in early blind humans have also shown smaller visual structures. For example, V1 area was smaller in anophthalmic compared with normally sighted individuals (Andelin et al., 2018). Moreover, congenitally blind humans showed smaller volumes compared with sighted controls for the optic tracts, DLG, optic chiasm, V1 and V2 (Noppeney et al., 2005; Pan et al., 2007; Park et al., 2009; Ptito et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second hypothesis seems intuitive as the protracted development of pathway maturation can expand territory into the postnatal ages, which can subsequently be shaped by environmental input. 140 These different hypotheses were proposed several years ago but the limitations of methods available to study the evolution of connections precluded their investigation in much detail.…”
Section: Evolution Of Developmental Timing In Connections Across Spmentioning
confidence: 99%